2015
DOI: 10.1111/jfr3.12190
|View full text |Cite
|
Sign up to set email alerts
|

A mitigation strategy for reducing flood risk to highways in arid regions: a case study of the El‐Quseir–Qena highway in Egypt

Abstract: During the past 20 years, there has been a rapid increase in tourism development along the Red Sea coast of Egypt. In the resort of Hurghada, for example, the number of hotel rooms increased from a few hundred in 1989 to 35 000 in 2004, and the entire Egyptian Red Sea coastline has experienced growth. Accordingly, car and lorry traffic between the major cities of Upper Egypt and the Red Sea coast along the El-Quseir-Qena highway has increased tremendously. The road provides access to tourist destinations and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Protection against flood of infrequent occurrence is uneconomical due to large investment required to get small profits and thus there is a certain volume of flood hazard participated. Abd-El Monsef, H.A., 2015, [1] demonstrated that the El Quseir-Quena highway could possibly be harmed by Wadi El-Ambagi flash flood at18 locations. These locations exist where sub basin of Wadi El-Ambagi convey water squarely to highway.…”
Section: Economics Of Flood Mitigationmentioning
confidence: 99%
“…Protection against flood of infrequent occurrence is uneconomical due to large investment required to get small profits and thus there is a certain volume of flood hazard participated. Abd-El Monsef, H.A., 2015, [1] demonstrated that the El Quseir-Quena highway could possibly be harmed by Wadi El-Ambagi flash flood at18 locations. These locations exist where sub basin of Wadi El-Ambagi convey water squarely to highway.…”
Section: Economics Of Flood Mitigationmentioning
confidence: 99%
“…The modeling of flash floods is a crucial tool for managing and mitigating floods [1,[37][38][39][40][41][42]. Numerous studies have mapped flood-prone areas using a variety of methodologies, such as [9,[43][44][45][46] have used traditional morphometric analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have explored strategies for flood management. Regrettably, recent studies consistently ignore the effects of climate change on water quality while developing flood risk management strategies (Abd-El Monsef 2018;Abdulrazzak et al 2019;Abdeldayem et al 2020;Fatahi Nafchi et al 2021;Hafshejani et al 2019), which is particularly common in developing countries because of a lack of financial resources. This lack in quality is commonly caused by increased precipitation washing away more pollution to water bodies or by extreme droughts increasing the concentration of pollutants in water bodies (Abd-El Monsef 2018;Abdulrazzak et al 2019;Abdeldayem et al 2020).…”
Section: Introductionmentioning
confidence: 99%